Analytical and functional approaches to assess the immunogenicity of gluten proteins - Mamone, Gianfranco; Di Stasio, Luigia; Vitale, Serena; Picascia, Stefania; Gianfrani, Carmen (Frontiers in Nutrition, 2023)
Gluten proteins are the causative agents of celiac disease (CD), a lifelong and worldwide spread food intolerance, characterized by an autoimmune enteropathy. Gluten is a complex mixture of high homologous water-insoluble proteins, characterized by a high content of glutamine and proline amino acids that confers a marked resistance to degradation by gastrointestinal proteases. As a consequence of that, large peptides are released in the gut lumen with the potential to activate inflammatory T cells, in CD predisposed individuals. To date, several strategies aimed to detoxify gluten proteins or to develop immunomodulatory drugs to recover immune tolerance to gluten are under investigation. This review overviews the state of art of both analytical and functional methods currently used to assess the immunogenicity potential of gluten proteins from different cereal sources, including native raw seed flours and complex food products, as well as drug-treated samples. The analytical design to assess the content and profile of gluten immunogenic peptides, described herein, is based on the oral-gastro-intestinal digestion (INFOGEST model) followed by extensive characterization of residual gluten peptides by proteomic and immunochemical analyses. These approaches include liquid chromatography–high-resolution mass spectrometry (LC-MS/MS) and R5/G12 competitive ELISA. Functional studies to assess the immune stimulatory capabilities of digested gluten peptides are based on gut mucosa T cells or peripheral blood cells obtained from CD volunteers after a short oral gluten challenge.